Performance of the Corruption Eradication Commission of the Republic of Indonesia - Randongkir, Lidia Vega; Zainal, Veithzal Rivai; Hakim, Aziz (Jurnal Indonesia Sosial Sains, 2025)
The Corruption Eradication Commission (KPK) is a state institution that has the main task of eradicating corruption in Indonesia. Since 2003 the Institute has been established as an independent institution to fight corruption despite facing various internal and external challenges. The performance of the KPK can be seen from several main aspects, including the number of cases handled, the effectiveness of investigations and investigations, and prevention efforts carried out through education and socialization to the community. In addition, the success of the KPK is also measured by the extent to which this institution can maintain its independence in the face of political and social pressure. However, the KPK's performance is not free from controversy, especially in terms of internal policies, supervision of public officials, and relations with other state institutions. Evaluation of KPK performance requires a comprehensive analysis of factors that support and hinder its effectiveness, including regulatory changes, human resources, and technology implementation. On the other hand, the role of the KPK in strengthening the legal system and encouraging an anti-corruption culture in Indonesia remains a hope for the public to create clean, transparent, and accountable governance. The KPK's performance continues to grow with internal reforms and employee capacity building through training and results-based learning. Nevertheless, the challenges in eradicating corruption are still large, and the KPK must continue to adapt to existing social, political, and economic dynamics in order to achieve its goals to the maximum. This study aims to see how the Corruption Eradication Commission (KPK) performs in eradicating corruption in Indonesia. Through secondary data analysis and interviews with KPK employees, this study identifies various challenges faced by the KPK and the achievements that have been obtained. The results of the study show that although the KPK has succeeded in uncovering major corruption cases, political challenges and limited human resources are still the main obstacles in its performance. This research also provides recommendations to increase the effectiveness of the KPK in facing existing challenges.